2015
DOI: 10.1080/09205063.2015.1103590
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable DNA-enabled poly(ethylene glycol) hydrogels prepared by copper-free click chemistry

Abstract: Significant research has focused on investigating the potential of hydrogels in various applications and, in particular, in medicine. Specifically, hydrogels that are biodegradable lend promise to many therapeutic and biosensing applications. Endonucleases are critical for mechanisms of DNA repair. However, they are also known to be overexpressed in cancer and to be present in wounds with bacterial contamination. In this work, we set out to demonstrate the preparation of DNA-enabled hydrogels that could be deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 55 publications
2
41
0
1
Order By: Relevance
“…Further analysis by scanning electron microscopy shows that the casting process of the DNA hydrogel using a flat foil‐cover yields a DNA material with a flat surface and minor wrinkles (Figure B I). Analysis of gel cross‐sections (Figure B II) revealed honeycombed structures which form the bulk of the material and show similar morphologies of other hydrogels …”
Section: Resultsmentioning
confidence: 77%
“…Further analysis by scanning electron microscopy shows that the casting process of the DNA hydrogel using a flat foil‐cover yields a DNA material with a flat surface and minor wrinkles (Figure B I). Analysis of gel cross‐sections (Figure B II) revealed honeycombed structures which form the bulk of the material and show similar morphologies of other hydrogels …”
Section: Resultsmentioning
confidence: 77%
“… 230 , 234 , 236 , 237 This cytocompatibility of SPAAC reactions is particularly attractive, as is the lack of ROS generation, enabling the efficient functionalization and cross-linking of hydrogels with complementary DNA strands. 238 …”
Section: Chemical Conjugationmentioning
confidence: 99%
“…In addition to the five biomedical hydrogels cited above, research has led to the development of a number of other novel hydrogels, including DNAenabled hydrogels, and magnetic hyaluronate hydrogels [98,99]. DNA-enabled hydrogels have been synthesized through the reaction of dibenzocyclooctyne-functionalized multiarm poly(ethylene glycol) with azide-functionalized single-stranded DNA in aqueous solutions by copper-free click chemistry (Figure 4) [98]. Besides, the hydrogel contained with the adipose-derived stem cells has been reported that can augment diabetic wound healing [100].…”
Section: Double Network Hydrogels Double Network (Dn)mentioning
confidence: 99%